A monitoring digital twin for services of controlled environment agriculture (2021)
Due to the already known problem about feeding the world's population in the next decades, the improvement of agricultural production systems has been widely explored, with technology being the main tool to create viable solutions like smart farming systems. Therefore, now it is common to find in the literature different proposals about how to implement these systems. Based on this, one of the possible solutions for the development of a smart farming system is the implementation of a Digital Twin (DT). However, implementing a DT could be a complex task since it requires skills in different areas (IoT knowledge, advance programming skills, agriculture expertise, and user interface design experience). Hence, the purpose of this work is to propose an architecture that allows for the implementation of a DT easily with monitoring functions (which is known as a Monitoring DT). It was developed to hold services for climate monitoring, display the state of the system, and plant management, and its implementation is based on a digital transformation model for the industry 4.0.